The Association between Peace and Life Expectancy: An Empirical Study of the World Countries - Vahid Yazdi Feyzabadi; Aliakbar Haghdoost; Mohammad Hossein Mehrolhassani; Zahra Aminian (Tehran University of Medical Sciences, 2015)
Background: Although theoretically peace affects health, few published evidence for such an association was empirically available. This study aimed to explore the association between peace and life expectancy (LE) among the world countries. Methods: In an ecological study and using random effects regression model, we examined the association between peace and LE among world countries between 2007 and 2012. The LE at birth and global peace index (GPI: a score between 1 and 5, higher score means lower peace) were selected as outcome and main predictor variables, respectively. We adjusted their association for the gross national income (GNI) per capita and education index (EI). Data were obtained from the Institute for Economics and Peace (IEP) and UNDP (United Nations Development Programme (UNDP). Numbers of included countries were 158 based on the available data. Results: GPI had a negative, considerable, and statistically significant effect on LE (standardized coefficient -0.039; 95% CI: -0.058, -0.019). This association was also significant even after the adjustment for EI (-0.019; 95% CI: -0.035, -0.003), GNI (-0.035; 95% CI: -0.055, -0.015), and both EI and GNI (-0.017; 95% CI: -0.033, -0.001). The full model showed that around 0.61 of the variation of LE among countries may be explained by the GPI, EI and GNI per capita. Conclusion: The contribution of peace as a global determinant of LE was empirically considerable even after the adjustment for the economic and education levels of countries. This implies that governments should make efforts to settle peace through implementing good governance based on interactions with both public and other countries.